(3aJM GdLdjd aj TQM eNJUQ Ndjds - (3eMeO Hf EHQGgje GdJJGFi , CHh YHO Gddg , TeS GdOjfs; (3Ndjd Hf ESMGb Hf ehSi, VjGA GdOjf GdoLrfpOj GdeGdcj GdeUQj,J (B776 (3g` s ((3eMeO Hf eMeO Hf aGVd SHW aGQS s)
(3ChdgG (B:s
(3HGH PcQ ajg GdELGQI hcQG GdOhGH hGdMeGe hGdOGQ hGdCQV heG HJYdb HPdc , hgj HcSQ GdgeRI , hgj eCNhPI ef GdCLQ , hgh GdKhGH s
(3BNQgG (B:s
(3jfJgi HHGH ai GdaQGFV s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eDQN SfI (B1148 (3hYKeGf Hf SfO GdeGdci eDQN SfI (B1234 (3hMGeO GdYeGOi eDQN (B1163s
(3fSNI bOjeI eUMMI s
(3HYV cdeGJgG hahGUdgG HGdMeQI s
(3MhGagG eJBcdI s
Keywords: (3Gdabg GdeGdcjs